THE EFFECTIVENESS OF THE IMPLEMENTATION OF EXPERIENCE, LANGUAGE, PICTORIAL, SYMBOL, AND APPLICATION (ELPSA) IN MATHEMATICS LEARNING BASED ON BRUNERS THEORY TO CLASS VII STUDENTS AT SMPN 29 IN MAKASSAR - St Syahdan (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The research is experiment. The research design is One-Group Pretest Posttest Design. The research employed two experiment classes, namely class VII.1 consist of 29 students and class VII.2 consist of 33 students chosen by using simple random sampling technique. Both classes were given the same treatment, namely experience, language, pictorial, symbol, and application in Mathematics learning based on Bruner’s theory. Data collecting techniques were learning result test, observation sheet, and questionnaire sheet. Data analysis employed descriptive statistic, inferential statistic, and effectiveness analysis. The results of the research indicate that: 1) Mathematics learning result of  class VII students at SMPN 29 in Makassar after the implementation of experience, language, pictorial, symbol, and application in Mathematics learning based on Bruner’s theory is in high category, the improvement of Mathematics learning result (gain score) of class VII students at SMPN 29 in Makassar is significant and in high category. Mathematics learning result of class VII students at SMPN 29 in Makassar after the implementation of experience, language, pictorial, symbol, and application in Mathematics learning based on Bruner’s theory has not reached classical completeness; 2) the students activity with the implementation of experience, language, pictorial, symbol, and application in Mathematics learning based on Bruner’s theory is in active category; and 3) the students response toward the implementation of experience, language, pictorial, symbol, and application in Mathematics learning based on Bruner’s theory tended to be in positive category. Learning effectiveness score reveals that the implementation of experience, language, pictorial, symbol, and application is fairly effective in Mathematics learning based on Bruner’s theory to class VII students at SMPN 29 in Makassar